2017
DOI: 10.1103/physrevb.95.115413
|View full text |Cite
|
Sign up to set email alerts
|

Local and long-range realizations of a spin-reorientation surface phase transition

Abstract: The spin reorientation transition of an ultrathin film from perpendicular to in-plane magnetization is driven by a competition between dipole and anisotropy energies. In situ measurements of the magnetic susceptibility of Fe/2 ML Ni/W(110) films as a function of Fe coverage, made as the films are deposited at constant temperature, show two clear peaks; one at the long-range and one at the local realization of the transition. In the long-range realization, the susceptibility probes the striped domain pattern th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…This model is developed in ref. (28) and shown to give an excellent quantitative description of the first peak in the experimentally measured susceptibility.…”
Section: B Local Metastable Magnetic Statementioning
confidence: 92%
See 3 more Smart Citations
“…This model is developed in ref. (28) and shown to give an excellent quantitative description of the first peak in the experimentally measured susceptibility.…”
Section: B Local Metastable Magnetic Statementioning
confidence: 92%
“…Similar measurements are analyzed quantitatively in ref. (28). The two peaks are the magnetic response at the local (near 1 ML) and the global (near 3 ML) realizations of the same reorientation transition.…”
Section: B Local Metastable Magnetic Statementioning
confidence: 95%
See 2 more Smart Citations
“…The error in the calibration is 5%. A previous study has shown that the flux calibration is linear in ion current, and stable in time over the time periods required to grow films while the magnetic susceptibility is being measured in real time 32 . For this type of measurement, the uncertainty along the deposition axis derived linearly from the deposition time is entirely accounted for by the uncertainty in the original flux calibration using AES.…”
Section: Experimental Methodsmentioning
confidence: 99%